Didactic Transposition in Reading Material : Linking Knowledge to be Taught and Assessment for Learning - Maulani, Hikmah; Syafei, Isop; Muthmainah, Nur (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2025)
This study aims to elaborate on the assessment of instructional planning (lesson plan), particularly how planning emerges from the teacher's internal didactic transposition. It focuses on the diffusion of knowledge by teachers from the curriculum and textbooks into the form of teaching modules or lesson plans. A qualitative approach through phenomenological research method was employed in this study. The data sources include the Arabic language teaching module for Grade 3 Madrasah Ibtidaiyah in Bandung and Arabic language teacher as participants. The selection of one Arabic teacher as a participant in this study can be justified methodologically with a purposive sampling approach. Data collection techniques consisted of document analysis and in-depth interviews, followed by a praxeological review as an analytical tool. The assessment results identified learning barriers faced by students in the Qiraah (reading) skill material. In this context, internal didactic transposition defined as the transformation of theoretical material into teaching practice plays a crucial role in aligning instructional content with students’ needs and learning objectives. The process of internal transposition in Qiraah instruction positively impacts students’ reading skills, especially when teaching materials are adapted contextually and made relevant to the students’ proficiency levels. These findings pave the way for deeper investigation into the influence of teacher-student verbal exchanges and teaching approaches on students’ comprehension of vocabulary and their reading strategies in Arabic text-based instruction.